LECTURERS AND STUDENT TEACHERS WITH HEARING IMPAIRMENTS’ OWN PERCEPTIONS ON ACADEMIC PERFORMANCE: A CASE STUDY OF KITWE COLLEGE OF EDUCATION - ZAMBIA (Isagoge - Journal of Humanities and Social Sciences, 2021)
The level of education attained by students is dependent on their ability to understand learnt concepts and demonstrate their acquired knowledge and skills in problem solving as well as their performance academically. This study sought to investigate the perceptions of lecturers on academic performance of student teachers with hearing impairments. A descriptive case study was used as research design. The study sample included three (3) Lecturers and four (4) student teachers with hearing impairments making the total of seven (7) participants who were purposively sampled. Data was generated using interviews and analysed qualitatively using thematic analysis techniques based on emerging themes from the study. The study revealed that lecturers perceived student teachers with hearing impairments as average and below-average performers academically. The study further revealed that student teachers with hearing impairments had mixed feelings towards their academic performance and perceived their academic performance as being influenced by their inability to understand concepts as well as lecturers’ inability to handle them appropriately. The study recommended the need by educators of students with hearing impairments to have positive perception towards students in order to instill self-positive regard in students. The study further recommended need for lecturers to adapt tests and examinations items in order to accommodate deaf student teachers.
Keywords: Academic performance; Hearing impairment; Perception; Student teacher